GREEBO: Sustainability Eco-Friendly Marketing as Shortcuts for SMEs to Compete in The 5.0 Society Era - Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra (Journal of International Conference Proceedings, 2022)
Purpose: Improve business performance by implementing a eco-friendly marketing sustainability model to penetrate the international market in the 5.0 society era. Methodology: The research method is an exploratory qualitative approach by collecting data based on in-depth interviews with related informants. The sampling technique is purposive sampling, in which the main criteria are SMEs assisted by the Central Java Government. The research analysis flow is data collection, data reduction, data presentation, and concluding. Findings: The results show the "GREEBO" solution model can be implemented in two ways, including (1) education and increasing green marketing knowledge; (2) mentoring and business model development. Research Limitation: The research object only SMEs in several city, so it can’t generate the whole situation in province. Improving SMEs business performance through the government's online single submission programs, so another government can adopt the "GREEBO" model. Practical implications: Improving SMEs business performance through the government's online single submission programs, so another government can adopt the "GREEBO" model. Originality/value: Eco-friendly marketing is the answer to internationalization several obstacles of SMEs facing the 5.0 society era market dynamics.